Relating Systems Thinking and Design III - Forlizzi, Jodi; Sevaldson, Birger; Ryan, Alex (FormAkademisk, 2017)
This special issue of Form Akademisk captures some of the systemic design thinking and research presented at the RSD3 conference, held in Oslo, Norway in 2014, and the RSD4 conference, held in Banff, Canada in 2015. These two conferences offered a range of submissions encompassing the fields of design, systemics, public policy, healthcare, and other domains. This body of work explores the emerging renaissance of systems thinking in design. The papers presented here are responses to the world we live and design in, a world that is increasingly complex and increasingly problematic for those in government, industry and academia alike. We believe that the thinking and intervention developed at RSD3 and RSD4 is well poised to meet these challenges. In this issue, we offer two sets of papers; the first set focuses on frameworks and organizing concepts, and the second set focuses on methods and tools to aid in systemic design.